Emergency Endovascular Interventions on Descending Thoracic Aorta: A Single-Center Experience. (3rd January 2023) - Buczkowski, Piotr; Puslecki, Mateusz; Ligowski, Marcin; Dabrowski, Marek; Stefaniak, Sebastian; Fryska, Zuzanna; Kulesza, Jerzy; Juszkat, Robert; Jemielity, Marek; Perek, Bartlomiej
Abstract : Background . Implementation of emergency endovascular aortic repair provides an attractive opportunity in the treatment of complicated acute aortic syndromes involving descending aorta. Aim . The aim of this study was to analyze the effectiveness of thoracic endovascular aortic repair (TEVAR) for the treatment of acute surgical emergencies involving the descending thoracic aorta. Methods . A retrospective review of the medical records of all patients undergoing TEVAR in a single center since 2007 was undertaken. Patients with the aortic disease treated on emergency inclusion criteria were complicated spontaneous acute aortic syndrome (csAAS), traumatic aortic acute injuries (TAIs), and other indications requiring emergent intervention. Technical and clinical success with patient mortality, survival, and reoperation rate was evaluated according to Society for Vascular Surgery reporting standards for thoracic endovascular aortic repair (TEVAR). Results The emergency interventions were necessary in 74 cases (51.0%), including patients with the complicated spontaneous acute aortic syndrome (csAAS) (64.8%; n  = 48) and traumatic aortic acute injuries (TAIs) (31.1%). In addition, in one case aortic iatrogenic dissection (AID) and in 2 other fistulas after the previous stent graft, implantations were diagnosed. All procedures were done through surgically exposed femoral arteries while 2 hybrid procedures required additional approaches. The primary technical success rate was 95.9%, in 3 cases endoleak was reported. The primary clinical success occurred in 94.5%. All patients survived the endovascular interventions, whereas during in-hospital stay one of them died due to multiorgan failure (early mortality 1.3%). During the follow-up period, lasting 6 through 164 months (median 67), 11 patients died. Annual, five- and ten-year probability of survival was 86.4 ± 0.04%, 80.0 ± 0.05%, and 76.6 ± 0.06%, respectively. However, the rate of 5-year survivors was significantly higher after TAI (95.2%) than scAAS (63.4%) (p = 0.008 ). Early after the procedure, one individual developed transient paraparesis (1.3%). No other serious stent-graft-related adverse events were noted within the postdischarge follow-up period. Conclusions . Descending aortic pathologies requiring emergent interventions can be treated by endovascular techniques with optimal results and low morbidity and mortality in an experienced and dedicated team.